2016
DOI: 10.1080/1067828x.2016.1242100
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Patterns of Substance Use and Delinquency: A Latent Transition Analysis

Abstract: This study explores gender-specific patterns and transitions of adolescent substance use and delinquency in a sample of youths at ages 12, 15, and 18 (N = 803). Latent transition analysis identified “Primary Delinquent,” “Delinquency and Substance Use,” and “Low Risk” classes. Females were less likely to be in the “Primary Delinquent” class at age 12 than males. From 15 to 18, females were approximately equally likely to transition from “Primary Delinquent” to both other classes, whereas males were more likely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 55 publications
0
16
0
1
Order By: Relevance
“…The self/parent discrepancies of conduct problems were associated with both grades and genders. Delinquency, defined as conduct that is out of accord with accepted behavior, was more common in early adolescence (age 12) among males than females, 18 and male adolescents tend to hide their problems of behavior for their parents rather than females. The self/parent discrepancy of hyperactivity/inattention was associated with grades.…”
Section: Discussionmentioning
confidence: 99%
“…The self/parent discrepancies of conduct problems were associated with both grades and genders. Delinquency, defined as conduct that is out of accord with accepted behavior, was more common in early adolescence (age 12) among males than females, 18 and male adolescents tend to hide their problems of behavior for their parents rather than females. The self/parent discrepancy of hyperactivity/inattention was associated with grades.…”
Section: Discussionmentioning
confidence: 99%
“…Although risk factors for substance use are somewhat similar for both genders, there is evidence that gender modifies the effect of social and peer factors on adolescent substance use [4]. Boys and girls differ in both exposure and response to factors, such as family and peer relations, school attachment, academic achievement, victimisation and social neighbourhood [8, 9]. In fact, a review focusing on risk factors influencing drinking progression among adolescents suggests that boys are more vulnerable to substance use because of social factors like higher tolerance, social expectation in use, and higher influence of parental drinking, while girls display higher permeability to parental control [10].…”
Section: Introductionmentioning
confidence: 99%
“…There are several reports in the literature on the close relationship between adolescent substance use and antisocial behaviours, both cross-sectionally [2628] and longitudinally [2932]. A study on substance use and delinquency clustering from adolescence to early adulthood identified a pattern of concurrent delinquency and substance use, in addition to a low risk and primary delinquent classes [31]. Using data from the 1970 British Cohort Study, Akasaki et al [27] found a risky behaviour class in 16-year-old adolescents characterised by smoking, binge drinking and involvement in physical fighting.…”
Section: Discussionmentioning
confidence: 99%